Identifying the corrupt cog in the wheel: Dimensions of supply chain logistics and cross-country corruption - Rajeev K. Goel; Ummad Mazhar; James W. Saunoris (Australian Economic Papers, 2020)
Reliable supply chains are crucial to the competitiveness, survival and profitability of businesses. While various aspects of supply chain logistics have been studied, their impacts on corrupt activity have not been fully understood. This paper examines the impact of the different stages of supply chain logistics on corruption. Besides adding insights into channels of potential corruption or rent-seeking, the research identifies potential stages of bureaucratic holdups related to the supply chain and can prove useful in the formulation of a more effective corruption-control policy. We use data for about 150 nations over the period 2000–2018 and the econometric methodology controls for potential reverse feedback from corruption to logistics. Our results show that an improvement in overall logistics performance reduces cross-country corruption, with individual dimensions of logistics having a differential corruption-reducing impact. The main policy implication is that governmental efforts to reduce supply chain bottlenecks will have positive spillovers in terms of reduced corruption.
Keywords: K42; L91; L98; 330; corruption; COVID-19; economic freedom; infrastructure; internet; logistics; shipments; supply chain; timeless; tracking; customs